Relationship between office and ambulatory blood pressure and various stress coping strategies in young adults - Yu. M. Yufereva; Ya. A. Naumov; R G. Timofeev; A. O. Shevchenko (Российский кардиологический журнал, 2024)
Aim. To study the relationship between office and ambulatory blood pressure (BP) and various stress coping strategies in healthy young adults.Material and methods. The design of the cross-sectional study included individuals of health status groups I or II aged 20 to 29 years with office BP <140/90 mm Hg. All individuals included in the study underwent office BP measurement and 24-hour ambulatory BP monitoring (ABPM). To determine the frequency of coping strategies, a Ways of Coping Questionnaire was used. For statistical analysis, the Stattech program, version 4.0.6 (Russia) was used.Results. The study included 347 participants, including 101 (29,1%) males; the median age was 22 (21-23) years. Linear dependencies were established between office BP and various ABPM parameters with three stress coping strategies: confrontation, avoidance, and seeking social support. The frequency of confrontation correlated with the greatest number of parameters, both assessed in office BP and ABPM. A direct dependence was noted between confrontation and office systolic blood pressure (SBP) (ρ=0,109; p=0,042) and diastolic blood pressure (DBP) (ρ=0,174; p=0,001), as well as average 24-hour SBP (ρ=0,120; p=0,025) and average day-time SBP (ρ=0,128; p=0,017). The avoidance frequency also directly correlated with the level of office DBP (ρ=0,158; p=0,003). With an increase in avoidance use by 1 point, clinical DBP increases by 0,13 mm Hg. At the same time, an inverse linear relationship was established between the strategy of seeking social support and night-time DBP (ρ=-0,112; p=0,036). With an increase in the frequency of seeking social support by 1 point, a decrease in the average night-time DBP by 0,07 mm Hg is expected.Conclusion. In young people, the level of office and outpatient BP linearly depends on the frequencies of using three models of coping behavior: confrontation, avoidance, and seeking social support.